(untitled) (Ameghiniana, 2018)
The Early Cretaceous marine deposits of the Agrio Formation are widely distributed in southern Mendoza and Neuquén provinces, Argentina. The stratigraphic distribution of upper Valanginian to upper Hauterivian organic-walled dinoflagellate cysts was evaluated at the Agrio Formation, at Bajada del Agrio locality. The assemblages exhibit a relatively moderate to low diversity and those with greater abundance are dominated by a small number of species such as Circulodinium distinctum, Cribroperidinium spp., Exochosphaeridium spp., Florentinia mantellii, Kiokansium unituberculatum, and Oligosphaeridium complex. Three diagnostic bioevents of lowest (LO) and highest (HO) stratigraphic occurrences of taxa calibrated with the local ammonoid zonation were identified for the Early Cretaceous of the Neuquén Basin: the LO of Callaiosphaeridium sp. (base of Holcoptychites neuquensis Zone, earliest Hauterivian), the LO of Cymososphaeridium validum (uppermost Hoplitocrioceras gentilii Zone, upper early Hauterivian) and the HO of Cymososphaeridium validum (lowermost Crioceratites diamantensis Zone, late Hauterivian). The studied assemblages are compared with Early Cretaceous assemblages from the Northern Hemisphere. In general, the association of dinoflagellate cysts together with the selected diagnostic species exhibit a clear affinity with those of the Mediterranean region.